The Co-operative: Good with schools?. (January 2015) - Coates, Max
The article is a summary of a small-scale research project which considers the formation of Co-operative Trust Schools. This was carried out in 2013 at a time when the number of schools becoming Academies and Trust Schools through the Co-operative College was burgeoning. Through questionnaire, interview, documentary analysis and exploration of websites, the research has sought to build up a picture of this Movement. A number of emergent issues are identified. These include the nature of new spaces for schools to form networks which provide a half-way house between the much tighter academy chains and the individual stand-alone academies and trust schools and the 'places' within the governance landscape within which they can do this. Perhaps the most challenging is the sometimes tenuous link between the value-centric Co-operative Movement and the values declared by these academies. It is suggested that the development of these academies with a connection with Co-operativism is more an association than a movement.